(3GdcQeGA haVd GdYWGA Ydi GdYSQs - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3eMeO Hf eMeO GdHGLhQj s)
(3ChdgG (B:s
(3cJH GdTjN CHhgdGd GdMSf Edi HYV GdQDSGA(B: (3LYd Gddg GdSjO aj MjR GdSdGeI, hLqddg GdTcQ s
(3BNQgG (B:s
(3heG CHWd GdEYOGoe MbkG dQGZH hdcfg aj MGdI GdjSQ ChLoH heKd gPG (B-(3CjOc Gddg(B- (3cKjQ, hajeG SbJg Edjc, caGjI dc s
(3GfXQ GdLRA GdChd GdQbe (B685 (3COHs
(3HBNQgG Jedc CMeO JjehQ SfI (B1321s
(3hgj fSNI ofbdJ Yf fSNI efbhdI Yf fSNI HNW GdYdGeI eMeO eMehO Hf GdJdGejO GdoJQocRj GdTfbjWjs
(3hHgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B240s
Keywords: (3GdCOHs